Hsa_circ_0020095 modulates chemoresistance of CRC in a PDO model - Xinyu Li; Xinyu Li; Tao Li; Tao Li; Yan Zhao; Yan Zhao; Junqi Shan; Yang Gao; Changchun Zhou; Yanlai Sun (Frontiers in Medicine)
BackgroundColorectal cancer (CRC) is the third most common malignant tumor type all over the world with high mortality. Chemoresistance of CRC leads to treatment failure and disease aggravation. We previously identified Hsa_circ_0020095 as a novel oncogene to promote progression and cisplatin-resistance in colon cancers by modulating the miR-487a-3p/SOX9 axis.MethodsPatient-derived organoids (PDOs) were generated from CRC patients and validated by H&E staining, immunohistochemistry (IHC), and whole exome sequencing (WES). Hsa_circ_0020095 was knocked down in PDOs by shRNA and the inhibition of hsa_circ_0020095 was determined using RT-qPCR. The RNA samples analyzed separately, and then pooled together for KEGG and GO analyses. The effects of knocking down hsa_circ_0020095 on drug-resistance of PDOs were examined using CellTiter-Glo®3D Cell viability assay. Finally, the underlying mechanism was explored by transcriptomic sequencing and subsequent bioinformatics analyses.ResultsFive organoid lines were successfully established from CRC patients using surgically resected tumor samples. PDOs resembled their parental tumor tissues in morphology, histopathology, and genetic alterations. Silencing of circ_0020095 resulted in remarkable inhibition of hsa_circ_0020095 in PDOs and reversed the resistance of PDOs to 5-FU and oxaliplatin. Mechanistically, hsa_circ_0020095 may function by modulating key pathways and biological functions involved in pathophysiological processes in CRC.ConclusionHsa_circ_0020095 modulates chemoresistance of CRC, which could potentially be explored as a therapeutic target for CRC treatment.